Gut dysmotility in children with neurological impairment: the nutritional management - Corsello, Antonio; Scatigno, Lorenzo; Govoni, Annalisa; Zuccotti, Gianvincenzo; Gottrand, Frédéric; Romano, Claudio; Verduci, Elvira (Frontiers in Neurology, 2023)
Intestinal motility disorders represent a frequent problem in children with neurological impairment. These conditions are characterized by abnormal movements of the gut, which can result in symptoms such as constipation, diarrhea, reflux, and vomiting. The underlying mechanisms leading to dysmotility are various, and the clinical manifestations are often nonspecific. Nutritional management is an important aspect of care for children with gut dysmotility, as it can help to improve their quality of life. Oral feeding, when safe and in the absence of risk of ingestion or severe dysphagia, should always be encouraged. When oral nutrition is insufficient or potentially harmful, it is necessary to switch to an enteral by tube or parenteral nutrition before the onset of malnutrition. In most cases, children with severe gut dysmotility may require feeding via a permanent gastrostomy tube to ensure adequate nutrition and hydration. Drugs may be necessary to help manage gut dysmotility, such as laxatives, anticholinergics and prokinetic agents. Nutritional management of patients with neurological impairment often requires an individualized care plan to optimize growth and nutrition and to improve overall health outcomes. This review tries to sum up most significant neurogenetic and neurometabolic disorders associated with gut dysmotility that may require a specific multidisciplinary care, identifying a proposal of nutritional and medical management.